2017
DOI: 10.3171/2017.5.peds17198
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into symptomatology of moyamoya disease in pediatric patients: survey of symptoms suggestive of orthostatic intolerance

Abstract: OBJECTIVEA specific population of young patients with moyamoya disease (MMD) persistently experience physical symptoms not attributable to focal ischemia. These symptoms, highly suggestive of orthostatic intolerance (also termed “orthostatic dysregulation”), were investigated and reported as potential determinants of quality of life in young MMD patients.METHODSForty-six patients (6–30 years of age) were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…Moreover vasculitis associated with rheumatologic disorders such as Wegener’s granulomatosis, systemic lupus erythematosus and juvenile rheumatoid arthritis could cause vertigo related to impaired vertebrobasilar circulation [ 61 ]. Indeed Moya-Moya disease, characterized by stenosis of the intracranial carotid arteries and basal collateral arteries, can be associated with vertigo on standing [ 62 ]. In these cases, a full physical examination usually helps to find out other associated neurologic deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover vasculitis associated with rheumatologic disorders such as Wegener’s granulomatosis, systemic lupus erythematosus and juvenile rheumatoid arthritis could cause vertigo related to impaired vertebrobasilar circulation [ 61 ]. Indeed Moya-Moya disease, characterized by stenosis of the intracranial carotid arteries and basal collateral arteries, can be associated with vertigo on standing [ 62 ]. In these cases, a full physical examination usually helps to find out other associated neurologic deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the combination of direct and indirect bypass is the optimal treatment in adult MMD [ 7 , 12 ]. It was reported that the annual risks of symptomatic infarction and hemorrhage were 0.2% and 0.4%, respectively, after analyzing 77 combined revascularization surgeries of 60 adult MMD patients and reported that the combined revascularization surgery resulted in satisfactory long-term improvement in clinical application, hemodynamic states, angiography, and prevention of recurrent stroke or TIA [ 13 , 14 ]. A potential mechanism is that direct revascularization could be effective at the early stage after surgery, maintaining its dominant role in collateralization, and these distal cerebral vessels progressively become partly or entirely occluded [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Relevant literature includes reports of improvement of headache following revascularization (direct, indirect anastomosis). In spite of revascularization and CBF improvement, many cases of pediatric moyamoya patients are left with the challenge to improve the persisting headache [2,6,7,9]. Regrettably, a Fig.…”
Section: ) Aspirin Is Highly Effective Against Headachesmentioning
confidence: 99%
“…The intractable headache can significantly reduce the quality of life (QOL) [6][7][8]. Its pathophysiological mechanisms remain unclear, although some of them such as stimulation of dural nociceptors by vasodilation of the transdural collaterals and chronic hypoxemia have been suggested [9]. In some cases, headaches are strong and associated with nausea at the time of waking up; however, they seem to be naturally alleviated around noon.…”
Section: Introductionmentioning
confidence: 99%